2012
DOI: 10.1002/clen.201100212
|View full text |Cite
|
Sign up to set email alerts
|

The Runoff Declining Process and Water Quality in Songhuajiang River Catchment, China under Global Climatic Change

Abstract: The runoff in Songhuajiang River catchment has experienced a decreasing trend during the second half of the 20th century. Serially complete daily rainfall data of 42 rainfall stations from 1959 to 2002 and daily runoff data of five meteorological stations from 1953 to 2005 were obtained. The Mann-Kendall trend test and the sequential version of Mann-Kendall test were employed in this study to test the monthly and annual trends for both rainfall and runoff, to determine the start point of abrupt runoff declinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…However, the specific changing characteristics were found to be various among the five sub river basins and different sub periods in our study. Apart from the decreasing trend in streamflow of the SRB reported by other researchers [27,42], our study identified a change-point of the year of 1974 for runoff. The results showed that the average runoff during the last 35 years declined in all sub river basins of the SRB when compared with that of the previous 15 years before 1974.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…However, the specific changing characteristics were found to be various among the five sub river basins and different sub periods in our study. Apart from the decreasing trend in streamflow of the SRB reported by other researchers [27,42], our study identified a change-point of the year of 1974 for runoff. The results showed that the average runoff during the last 35 years declined in all sub river basins of the SRB when compared with that of the previous 15 years before 1974.…”
Section: Discussionsupporting
confidence: 44%
“…In the past half century, climate in the SRB has become warmer and drier [6] and a large area of wetlands has degraded while farmland has been increasing rapidly within the river basin [26]. At the same time large-scale river engineering projects (primarily, construction of dams and ditches) were completed in the basin to meet the increased water use demand for agriculture, industry, and public [27]. A recent study [6] found a decreasing trend of discharge in all major tributaries of the SRB over the past half century.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is one of the main reasons for large‐scale shrinkage, fragmentation, and salinization of wetlands, especially in arid regions (Fay et al 2016; Zhang et al 2019). To reveal the pattern of climate change, a large number of researchers reconstructed historical temperature regimes for a series of different environmental types, different resolutions, different regions, and different starting and ending times (Mu et al 2012; Mitsch et al 2013; Zhang et al 2019). These results confirm the occurrence of climate change for the historic period.…”
Section: Drivers Of Hc Weaknessmentioning
confidence: 99%
“…The non-parametric Mann-Kendall statistical test has been widely used for trend detection in the time series of hydro-climatic data [29]. For a group of hydrological time series variables, X i (i = 1, 2, 3, ......, n), the Mann-Kendall test statistic S is calculated by:…”
Section: Trends Test To Detect Changes Of Precipitation Streamflow mentioning
confidence: 99%